Optical and Electronic Structure Calculation of Double Perovskites Ba2ErSbO6. (2017) - Kumar, Sujit; Kumar, Ajay; Himanshu, A.K.; Kumar, Uday; Poddar, P.; Sinha, T.P.
Abstract: The density function theory (DFT) under the generalized gradient approximation has been used to investigate the electronic structure of the double perovskite half metallic Ba2 ErSbO6 synthesized by the solid state reaction technique. Our results states that Ba2 ErSbO6 material behaves as insulators for the spin-up orientation and spin down orientation as found for the half metallic system and become insulating for both the orientation with DFT+U (at U=0.2Ry) Double perovskite belonging to the series Ba2 LnB′O6 (Ln = the lanthanide and Y 3+ and B′ = Nb 5+, Ta +, Sb 5+ ) are of the interest in the recent years due to their significance to both the fundamental research and the high potential for potential for technological applications [1-3]. These DPO's are widely used A as the substrate for the high-Tc superconductors, second harmonic generators, solid oxide fuel cell battery, etc. for the last one decade after the report of Sr2 FeMo6 demonstrating that its electronic structure only minority intrinsic spins are present at the Fermi level and that its exhibited intrinsic tunneling –type magneto resistance (TMR) at room temperature (RT) motivated the study of this material and triggered the interest of to prepare new perovskites which potentially could present half-metallic properties. As matter of fact, to predict a half metallic turned out to be a challenge, if some detailed treatment is not carefully conducted. In this work, Ba2 ErSbO6 (BES) double perovskite are highlighted and their electronic structures are investigated. Although such heavier metals (4d/5d/5f) diverse group A2 CMO6 materials are mostly characterized to be semiconductors, insulators, their electronic structures exhibit half-metallic features whatever by means of the generalized gradient approximation (GGA) calculations. Hence, the calculation of GGA+U, GGA+SOC and finally GGA+U+SOC is necessary to calculate the reasonable electronic structure. Here we present the GGA and GGA+U (at U=0.2Ry) approach for the calculation of electronic band structure of BES and optical studies.